2019
DOI: 10.1029/2019jg005339
|View full text |Cite
|
Sign up to set email alerts
|

Reduction‐Oxidation Potential and Dissolved Organic Matter Composition in Northern Peat Soil: Interactive Controls of Water Table Position and Plant Functional Groups

Abstract: Globally important carbon (C) stores in northern peatlands are vulnerable to oxidation in a changing climate. A growing body of literature draws attention to the importance of dissolved organic matter (DOM) in governing anaerobic metabolism in organic soil, but exactly how the reduction-oxidation (redox) activities of DOM, and particularly the phenolic fraction, are likely to change in an altered climate remain unclear. We used large mesocosms in the PEATcosm experiment to assess changes in peatland DOM and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 110 publications
1
20
0
Order By: Relevance
“…These patterns can be explained by abiotic and biotic factors: the intolerance of most fungi to anoxic conditions (Kavanagh, 2011) constraining most taxa to shallow peat, and the colocation of the dominant ErMF with their shallowly rooted Ericaceae hosts (Moore et al, 2002; Wallén, 1987). In contrast, the broad range of moisture niches, metabolic pathways and redox tolerance among soil prokaryotes (e.g., Bodelier & Dedysh, 2013; Lennon et al, 2012) and the strong sensitivity of prokaryote communities to changes in soil moisture (e.g., Bapiri et al, 2010; Barnard et al, 2013) explain their shift with WT treatments in both drier surface peat as well as at the acrotelm–catotelm boundary where redox conditions are most dynamic (Kane et al, 2019; Tfaily et al, 2018). These depth‐dependent effects indicate that WT and PFG are among the key shapers of the vertical physicochemical gradients that structure peatland microbial communities (Andersen et al, 2013; Artz et al, 2007; Lin et al, 2014), the activities of which then feed back to modulate carbon cycling along the peat profile (Chanton et al, 2009; Kane et al, 2019; Lin et al, 2014; Tfaily et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These patterns can be explained by abiotic and biotic factors: the intolerance of most fungi to anoxic conditions (Kavanagh, 2011) constraining most taxa to shallow peat, and the colocation of the dominant ErMF with their shallowly rooted Ericaceae hosts (Moore et al, 2002; Wallén, 1987). In contrast, the broad range of moisture niches, metabolic pathways and redox tolerance among soil prokaryotes (e.g., Bodelier & Dedysh, 2013; Lennon et al, 2012) and the strong sensitivity of prokaryote communities to changes in soil moisture (e.g., Bapiri et al, 2010; Barnard et al, 2013) explain their shift with WT treatments in both drier surface peat as well as at the acrotelm–catotelm boundary where redox conditions are most dynamic (Kane et al, 2019; Tfaily et al, 2018). These depth‐dependent effects indicate that WT and PFG are among the key shapers of the vertical physicochemical gradients that structure peatland microbial communities (Andersen et al, 2013; Artz et al, 2007; Lin et al, 2014), the activities of which then feed back to modulate carbon cycling along the peat profile (Chanton et al, 2009; Kane et al, 2019; Lin et al, 2014; Tfaily et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PEATcosm was a mesocosm experiment designed to test the influence of seasonal drought and PFG on peatland ecosystems. Detailed descriptions of the experimental design, peat characteristics, porewater chemistry and vegetation can be found in Kane et al (2019), Lamit et al (2017) and Potvin et al (2015). The experiment contained 24 ~1‐m 3 peat monoliths excavated from an oligotrophic acidic (pH = ~4) Sphagnum peatland in Minnesota, USA (47.07278°N, 92.73167°W), in May 2010.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A general pattern of DOC quality under water level alteration is that drainage increases DOC aromaticity and decreases DOC biodegradability (Wickland, Neff, and Aiken 2007;Hribljan et al 2014;Hansen et al 2016;Jassey et al 2018). Specifically, water table drawdown increases the occurrence and molecular weight of phenolics in DOC (Blodau and Siems 2012;Frank et al 2014;Lou et al 2014;Kane et al 2019), while rising water table decreases aromaticity and makes DOC more labile (Holl et al 2009;Hribljan et al 2014;Dieleman et al 2016b).…”
Section: Effects Of Water Level Alteration On Docmentioning
confidence: 99%
“…These species also transport oxygen into saturated peat enhancing microbial decomposition, resulting in relatively higher CO 2 emissions with sedge dominance (Shannon and White 1994;Silvan et al 2005;Garnet et al 2005;Strack et al 2006a;Fritz et al 2011;Green and Baird 2012;Robroek et al 2015;Jordan et al 2016;Marushchak et al 2016;Rupp et al 2019). A recent study found sedge roots are conducive to the generation of oxidized, larger compounds that serve as electron acceptors in anaerobic microbial decomposition, which increases CO 2 emissions (Kane et al 2019).…”
Section: Indirect Effects On Decomposition Via Plant-microbe Interactmentioning
confidence: 99%